The roles of attitudes towards learning and opposite sex as a predictor of school engagement: mixed or single gender education? - Erdoğdu, Mustafa Yüksel; Erdogdu, Mustafa Yüksel (Palgrave Macmillan Ltd, 2020)
Students' attitudes towards learning and their school engagement play important roles on the success of educational programs. Therefore, the main purpose of this research is to examine the roles of attitude towards learning and attitude towards the opposite sex as a predictor of school engagement and to determine the correlation between mixed gender education vs. single gender education and school engagement. Eight hundred and forty-three students (525 females and 318 males) who were studying in single gender or mixed gender schools were included in the research. Data were collected through School Engagement Scale, Attitude Scale towards Learning and Opposite Sex Attitude Scale. The Pearson moment correlation coefficient, multiple regression and stepwise regression were used to analyze the data. Findings showed that attitudes towards learning scores are the most predictive for school engagement. Results also showed that school engagement was higher in single gender schools for girls than in single gender schools for boys and mixed gender schools. The success of the student and the attitude towards the opposite sex were also variables that predict school engagement. The democratic attitude and education levels of parents also had important effects on students' school engagement. The findings have important implications for educational policy making and curriculum designs. Some general recommendations were made based on the findings.
WOS:000532404400002